1995
DOI: 10.1111/j.1432-1033.1995.tb20794.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Melanosomal Proteins with Melanin

Abstract: Melanin is deposited in melanosomes upon a proteinaceous matrix enveloped by a melanosomal membrane. Since melanin is highly detergent insoluble, we hypothesized that the detergent solubility of proteins of the melanosomal matrix might be inversely related to the state of melanosomal melanization. Immunoblotting analyses were performed on extracts of albino and black melanocytes to test this hypothesis. The protein products of the silver (si) and the pink-eyed-dilution (p) loci as well as other matrix constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
4
42
0
Order By: Relevance
“…Similar results were obtained in transiently transfected HeLa cells expressing OCA2, although processing in the Golgi seemed to be faster (Figure 1b). Note that processed OCA2 disappeared rapidly from detergent lysates in melanocytes, consistent with earlier results, suggesting close association with melanin (Donatien and Orlow, 1995), but much less rapidly in transfected HeLa cells. The reduction in M r resulting from PNGase F or endoH treatment of OCA2 was ϳ7 kDa, consistent with loss of two N-linked oligosaccharide chains.…”
Section: Molecular Biology Of the Cell 1466supporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were obtained in transiently transfected HeLa cells expressing OCA2, although processing in the Golgi seemed to be faster (Figure 1b). Note that processed OCA2 disappeared rapidly from detergent lysates in melanocytes, consistent with earlier results, suggesting close association with melanin (Donatien and Orlow, 1995), but much less rapidly in transfected HeLa cells. The reduction in M r resulting from PNGase F or endoH treatment of OCA2 was ϳ7 kDa, consistent with loss of two N-linked oligosaccharide chains.…”
Section: Molecular Biology Of the Cell 1466supporting
confidence: 90%
“…OCA2 was originally thought to localize predominantly to mature melanized melanosomes based on subcellular fractionation of melanocytes (Rosemblat et al, 1994), poor extraction by detergent from melanized melanocytes relative to nonmelanized melanocytes (Donatien and Orlow, 1995), and interpretation of results from confocal immunofluorescence microscopy (IFM) analyses (Toyofuku et al, 2002). Tyrp1-containing compartments in melanocytes from OCA2-deficient mice are less acidic than in wild-type melanocytes, suggesting that OCA2 not only localizes to melanosomes but also modulates their pH (Puri et al, 2000), although this interpretation is disputed because Tyrp1 does not localize to melanosomes properly in OCA2-deficient melanocytes (Manga et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the colocalization of Tyr and p in melan-c cells further strengthens our conclusions regarding the ER localization of p. However, it is still possible that a portion of total p may locate in other organelles. Previous experiments have shown that increasing melanin deposition is inversely proportional to p detection by Western blotting (Donatien and Orlow, 1995). Thus, mature melanosomes may still contain some p, which is not detectable by the techniques used in the current study.…”
Section: Discussionmentioning
confidence: 60%
“…Hypotheses regarding p function include the following: 1) p transports tyrosine into melanosomes (Lee et al, 1995). 2) p plays a structural role in melanosomes (Donatien and Orlow, 1995;Rosemblat et al, 1998) or is involved in melanosome biogenesis (Orlow and Brilliant, 1999). 3) p plays a role as a pH regulator in melanosomes and provides an optimal pH for Tyr activity (Puri et al, 2000;Brilliant, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation